Israel, Palestine - Dowty, Alan, 1940- (2023)
"A fully revised and updated new edition of this leading introduction to the Arab-Israeli conflict"--
Includes bibliographical references (pages 260-271) and index.
Keywords: Arab-Israeli conflict -- History; Jewish-Arab relations -- History; Palestinian Arabs; Zionism -- History; Israel -- Politics and government; West Bank -- Politics and government; Gaza Strip -- Politics and government; Jerusalem -- Politics and government